PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN ON ASSET (ROA) PADA PERUSAHAAN PT INDOCEMENT TUNGGAL PRAKARSA TBK PERIODE 2011-2020 - Rismanty, Vidya Amalia; Dewi, Iriana Kusuma; Sunarto, Ading (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of Current Ratio (CR), Debt To Equity Ratio (DER), and Total Asset Turnover (TATO) on Return On Assets (ROA) at PT. Indocement Tunggal Prakarsa Tbk period 2011-2020. The method used in this research is descriptive associative with a quantitative approach. The population in this study uses financial statements and for the sample reports in the form of balance sheets and profit and loss PT. Indocement Tunggal Prakarsa Tbk period 2011-2020. The results of this study indicate that partially the T test results show that the Current Ratio (CR) has a significant effect on Return On Assets (ROA), Debt to Equity Ratio (DER) partially has a significant effect on Return On Assets (ROA), and Total Asset Turnover. (TATO) partially significant effect on Return On Assets (ROA). F Test Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) simultaneously have a significant effect on Return On Assets (ROA) at PT. Indocement Tunggal Prakarsa Tbk.